Measurement of soil respiration and its isotope signature using an automated closed-chamber system - Downie, Matthew (Cranfield University, 2014)
A variety of methods is currently used for measuring soil and plant respiration and its isotope composition. Limitations found in the literature show a lack of a single set of specifications for these measurements. This report details a unique laboratory at Cranfield University (the Wolfson Field Laboratory - WFL) containing automated gas flux chambers attached to planted soil lysimeters and capable of providing near continuous measurements of gas fluxes and their isotope composition. The research in this thesis was concerned with the ability of the WFL to measure CO2 gas fluxes from plants and soil and their isotope composition. A specification for closed chamber methods was developed, the validity of these specifications tested, and the ability of the WFL to meet these specifications determined. The methods developed include a means of assessing the effects of gas loss processes both on the measured CO2 concentration and the measured isotopic signature within a defined volume. Measurements of plant and soil CO2 efflux in the WFL lysimeters and its isotope composition were used to infer the isotope signature of plant and soil respiration using Keeling plots. The results showed the specifications developed were valid although further work is required to determine the ability of the WFL to meet the isotope measurement specifications.
Keywords: Specifications; diffusion modelling; Keeling plots; diurnal variation; CO2 analysis